Optimizing yield, nitrogen uptake and nitrogen use efficiency in fluted pumpkin through fertilizer microdosing: Abstract, Intriduction, Materials and Methods, Results and Discussion, Conclusion, Acknowledgments - Olatoberu, Francis; Idowu, Mary; Oyedele, Durodoluwa; Oladoye, Christianah; Akinremi, Omotayo; Ponle, Ifeoluwa; Adebooye, Odunayo; Adekunle, Ojo (Journal of Agricultural Sciences (Belgrade), 2025)
Due to severely weathered soils and copious amounts of rainfall, the timing and rate of fertilizer application to enhance fluted pumpkin (Telfairia occidentalis) yields, nitrogen use efficiency, and recovery have been key concerns in Southwestern Nigeria. The experiment was conducted using a 2 x 2 x 5 Randomized Complete Block Split Plot Design (RCBSPD) with four varieties. Ilesa and Ogbomoso made up the main plot, whereas the timing of urea fertilizer application and the five nitrogen levels 0, 20, 40, 60, and 80 kg ha-1 made up sub-plots. The base application of 5 tons ha-1 organic fertilizer was added to (0, 20, 40, 60 kg ha-1) a week prior to planting. We calculated the biomass yield, recoveries, and nitrogen utilization efficiency. Regarding control, 20, 80 (kg N ha-1) urea, the fresh yield in tons ha-1 were 7.7, 9.4, 10.7, and 3.3, 8.3, 9.5 (kg N ha-1) for Ilesa and Ogbomoso. The highest nitrogen use efficiency (60.26 kg N ha-1) was obtained at the rate of 40 kg N ha-1 in Ilesa, and at the rate of 20 kg N ha-1 (61.91 kg N ha-1) in Ogbomoso. Higher fresh yield was obtained in Ilesa compared to the yield in Ogbomoso. It was determined that the best method for producing fluted pumpkin in Southwest Nigeria was to combine 5 tons of organic fertilizer with a microdosing of 20 to 40 kg N ha-1 as urea.